Cell formation and layout design with alternative routing: a multi-objective scatter search approach. (1st January 2013) - Jabal-Ameli, M. Saeed; Moshref-Javadi, Mohammad; Tabrizi, Behzad Bankian; Mohammadi, Milad
Cellular manufacturing is a technology to improve the productivity and flexibility of manufacturing systems. Cell formation and layout design are two main problems in designing cellular manufacturing systems (CMSs). Due to the interaction between the two problems, these problems must be solved simultaneously to obtain the optimal solution. The problem is formulated as three different mathematical models which differ with respect to layout constraints and backward movements. A multi-objective scatter search is proposed to solve the integrated cell formation and layout design problem in CMSs. We introduce a new solution representation which is used in the algorithm. The performance of the algorithm is compared with the epsilon-constraint method and a well-known multi-objective evolutionary algorithm, non-dominated sorting genetic algorithm II (NSGA-II). The proposed algorithm not only obtained better solutions in comparison to the solutions proposed by past authors, but also it performs better than NSGA-II.